(untitled) (Journal of EAHIL, 2016)
Since 1993, the CRO library has organized training courses on the use of information resources for the institute staff.Â However, recently the need to revise the proposals for meeting the educational needs of the scientific and clinical staffÂ has arisen. A practical approach was adopted: planning short weekly lessons focused on practical learning of a singleÂ instrument at a time. The course structure included a minimum number of lessons whose attendance was compulsory toÂ be chosen on the basis of individual professional interests of learners. With this approach, all instruments wereÂ compared and contextualized within a precise wider documentary search methodology. From the evaluation forms andÂ “narrative” feedback, it has emerged that both courses were perceived as “relevant” for increasing attendants’Â professional skills and had a positive impact on their professional practice.